Moving to a new job: The role of home equity, debt, and access to credit - Yuliya Demyanyk; Dmytro Hryshko; María José Luengo-Prado; Bent E. Sørensen (Federal Reserve Bank of Boston, 2016)
Using individual-level credit reports merged with loan-level mortgage data, we estimate how mobility relates to home equity when labor markets are weak or strong. We control for constant individual-specific traits with fixed effects and find that homeowners with negative home equity move to other metropolitan areas more than other homeowners. We use a dynamic quantitative model of consumption, housing, employment, and mobility to interpret our findings. The model illustrates that the gain from accepting a job in another area outweighs the cost of disposing of underwater property and replicates the data well.
Keywords: E21; J61; R23; 330